Screening of LAB strains and their co-culture fermentation with Bacillus subtilis of Cili fruit substrate: impact on γ-aminobutyric acid enrichment, key enzyme activities, bioactive and functional properties - Angelo Uriho; Jacob Ojobi Omedi; Cheng Chen; Kaiwen Chen; Shuning Zhang; Li Liang; Yan Xu; Ning Li; Weining Huang (Frontiers in Nutrition)
In this study, 20 lactic acid bacteria (LAB) strains were screened for glutamic acid decarboxylase activity (GAD); and used as co-culture starters with Bacillus subtilis to enrich the γ-Aminobutyric acid (GABA) content in Cili fruit. Changes in physiochemical properties, key enzyme activities, bioactive composition and functional properties in the co-culture fermented Cili fruit substrate was reported. Five of 20 LABs exhibited adequate GAD activity, but only three strains (Levilactobacillus brevis DS4-15: BsLb, Lactiplantibacillus plantarum N2-9: BsLp, Limosilactobacillus fermentum BT2-3: BsLf), enhanced the GABA content in Cili fruit at the optimized co-culture fermentation conditions. Compared to B. subtilis fermented substrate (Bs), a significant decrease in pH (4.89, except BsLf), increase in TTA (19.30–29.20 mL) was observed after co-culture fermentation of Cili fruit. Moreover, higher GABA (102.48–585 mg/kg), total phenol (256–275.17 GAE/g), total flavonoid (140.54–172.33 QE/g), and total free amino acid (2,278.37–6,191.39 mg/kg FW), but decreased vitamin C (740.48–960.59 mg/kg FW) content was observed after co-culture fermentation, especially in the order BsLf, then BsLp, and BsLb. Subsequently, the antioxidant activity and anti-hangover properties increased in BsLf, BsLp and BsLb compared to Bs and unfermented Cili fruit. The changes observed were attributed to LAB strains’ ability to alter pH during co-culture fermentation with B. subtilis which was optimal for increased enzyme activities of esterase, β-glucosidase, GAD, protease and ascorbate oxidase during co-culture fermentation (BsLf > BsLp > BsLb). This increased the release of bioactive metabolites in Cili fruit and enhanced its functional properties. These findings reveal that there was a synergy in co-culture fermentation which improved the bioactive and functional properties of Cili fruit as a novel GABA enriched ingredient for potential use in the food industry.